Practical Aspects of the Ligand-Binding and Enzymatic Properties of Human Serum Albumin - Kragh-Hansen, U.; Chuang, Victor; Otagiri, M. (Pharmaceutical Society of Japan, 2002)
Recent work with approaches like recombinant mutants and X-ray crystallography has given much new information about the ligand-binding properties of human serum albumin (HSA). The information increases the understanding of this unique transport and depot protein and could give a structural basis for the possible construction of therapeutic agents with altered HSA-binding properties. A tabulation of high-affinity binding sites for both endogenous and exogenous compounds has been made; it could be useful for the above-mentioned purpose, but it could also be of value when trying to predict potential drug interactions at the protein-binding level. Drug displacement is not always a complication to therapy; it can be used to increase the biological effect of a drug. However, due to rebinding at other sites, the increase in the free concentration of a displaced ligand can be less than expected.Drugs and drug metabolites can also interact covalently with HSA; thiol-containing drugs often bind to the single free cysteine residue of HSA, and glucuronidated drugs react irreversibly with other residues of the protein. Reversible binding of ligands is often stereospecific, and therefore immobilized HSA can be used to separate drug isomers. Albumin-containing dialysates are useful for extracorporeal removal of endogenous toxins and in the treatment of drug overdoses. HSA has different types of hydrolytic activities, which also can be stereospecific. The esterase-like property seems especially useful in converting prodrugs to active drugs in plasma.